Hypoxia, hypoxia-inducible transcription factors, and renal cancer - Schödel, Johannes; Grampp, Steffen; Maher, Eamonn R.; Moch, Holger; Ratcliffe, Peter John; Russo, Paul; Mole, David R. (European Urology, 2016)
Context Renal cancer is a common urologic malignancy, and therapeutic options for metastatic disease are limited. Most clear cell renal cell carcinomas (ccRCC) are associated with loss of von Hippel-Lindau tumor suppressor (pVHL) function and deregulation of hypoxia pathways. Objective This review summarizes recent evidence from genetic and biological studies showing that hypoxia and hypoxia-related pathways play critical roles in the development and progress of renal cancer. Evidence acquisition We used a systematic search for articles using the keywords hypoxia, HIF, renal cancer, and VHL. Evidence synthesis Identification of the tumor suppressor pVHL has allowed the characterization of important ccRCC-associated pathways. pVHL targets α-subunits of hypoxia-inducible transcription factors (HIF) for proteasomal degradation. The two main HIF-α isoforms have opposing effects on RCC biology, possibly through distinct interactions with additional oncogenes. Furthermore, HIF-1α activity is commonly diminished by chromosomal deletion in ccRCCs, and increased HIF-1 activity reduces tumor burden in xenograft tumor models. Conversely, polymorphisms at the HIF-2α gene locus predispose to the development of ccRCCs, and HIF-2α promotes tumor growth. Genetic studies have revealed a prominent role for chromatin-modifying enzyme genes in ccRCC, and these may further modulate specific aspects of the HIF response. This suggests that, rather than global activation of HIF, specific components of the response are important in promoting kidney cancer. Some of these processes are already targets for current therapeutic strategies, and further dissection of this pathway might yield novel methods of treating RCC. Conclusions In contrast to many tumor types, HIF-1α and HIF-2α have opposing effects in ccRCC biology, with HIF-1α acting as a tumor suppressor and HIF-2α acting as an oncogene. The overall effect of VHL inactivation will depend on fine-tuning of the HIF response. Patient summary High levels of hypoxia-inducible transcription factors (HIF) are particularly important in the clear cell type of kidney cancer, in which they are no longer properly regulated by the von Hippel-Lindau protein. The two HIF-α proteins have opposing effects on tumor evolution.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Clear cell renal cell carcinoma; Hypoxia; Hypoxia-inducible transcription factors; von Hippel-Lindau